1989
DOI: 10.1130/spe230-p131
|View full text |Cite
|
Sign up to set email alerts
|

Definition of tectonostratigraphic terranes in the Mauritanide, Bassaride, and Rokelide orogens, West Africa

Abstract: The West African orogens (Mauritanides, Bassarides, Rokelides) record a locally complex, polyphase, tectonothermal evolution. The earliest event corresponded to westward rifting of a continental fragment from the West African craton at ca. 700 Ma. This led to development of a rift-facies lithotectonic succession that included sedimentary units and intracontinental igneous sequences. Rifting must have been of limited extent because a western ensialic arc began to develop as early as 680 Ma. The associated conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Based on Ar/Ar dating, Lécorché et al (1989) and Villeneuve et al (2010) concluded that a 575-550 Ma or somewhat younger tectonothermal event occurred all along the west margin of the WAC, best expressed south of ca. 10°S (Rockelide orogen).…”
Section: The Bessaride-mauritanide Beltmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on Ar/Ar dating, Lécorché et al (1989) and Villeneuve et al (2010) concluded that a 575-550 Ma or somewhat younger tectonothermal event occurred all along the west margin of the WAC, best expressed south of ca. 10°S (Rockelide orogen).…”
Section: The Bessaride-mauritanide Beltmentioning
confidence: 98%
“…lat. 13°N it was reworked by the Variscan Mauritanide orogeny (Lécorché et al, 1989;Lytwyn et al, 2006;Villeneuve, 2008;Caby and Kienast, 2009;Villeneuve et al, 2010). The eastern units, thrust over the WAC, consist of low grade metasediments (with a Variscan overprint) that resemble the Neoproterozoic cover of the WAC, but with intercalated volcanics.…”
Section: The Bessaride-mauritanide Beltmentioning
confidence: 99%
“…In Sierra Leone, a suture may outcrop somewhere between the western boundary of the Rokel River Group and eastern boundary of the Kasila Group (Burke and Dewey, 1972;Burke et al, 1977) in a region partially bordered by mylonites and westerly-dipping thrust faults (Williams and Culver, 1982). Lécorché et al (1989) placed the suture along ductile shear zones between the Kasila Group and ''Kenema Assemblage''. The suture is cryptic south of the Rokel River Group outcrop where it separates the Kasila gneisses from the West African craton (Burke and Dewey, 1972).…”
Section: Tectonic Modelsmentioning
confidence: 98%
“…Earlier collision between the Kasila Group and this microcontinent/arc would then be followed by later Pan African collision between the Kasila-arc collage and West African Craton. , Ponsard et al (1988) and Lécorché et al (1989) devised similar tectonic models for evolution of the Mauritanides. According to their models, westward rifting of a continental fragment (Western Block Craton) from West Africa occurred around 700 Ma and was accompanied by emplacement of alkaline to tholeiitic basalts.…”
Section: Tectonic Modelsmentioning
confidence: 98%
See 1 more Smart Citation